PENGARUH LINGKUNGAN KERJA, STRES KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN BAGIAN PRODUKSI PADA PT. EKA DURA INDONESIA DI KABUPATEN ROKAN HULU - Septian, Shendy; Indarti, Sri; Chairilsyah, Daviq (Jurnal Tepak Manajemen Bisnis, 2019)
This research was conducted aimed at knowing the effect of the workenvironment, work stress, and job satisfaction on turnover intention at PT. EkaDura Indonesia in Rokan Hulu Regency. The benefits of research are expected tobe able to contribute to the benefits of the company and scientific facilities.The population in this study were all employees of PT. Eka Dura Indonesiain Rokan Hulu Regency. The research sample was all employees of PT. Eka DuraIndonesia, Rokan Hulu Regency, part of production. The method of datacollection is by using interviews and questionnaires. Data analysis techniquesusing multiple linear regression analysis.The results showed partially, work environment, work stress, and jobsatisfaction had a significant influence on turnover intention. Simultaneously, theindependent variables in this study were able to provide a significant influence on the turnover intention variable